MANAJEMEN BRAND IMAGE DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP LEMBAGA PENDIDIKAN ISLAM - Fakhruddin Al Farisy; Ulvia Fatkurin Fuad; Rohmat Hidayatulloh3 (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2024)
Brand image management has an important and significant to increase the competitiveness of Islamic educational institutions, where increasingly tight competition requires a strong and positive brand image to attract prospective students, parents, and the general public. Therefore, it is necessary to design an communication strategy and involve all elements of the institution to build and maintaining a solid brand image to competitiveness in the education market. This study uses a qualitative approach with a case study design. Data collection using in-depth interview techniques, observation and documentation. Checking the validity of the findings using the participation of researchers and triangulation. Research information from the institution's stageholders, especially the public relations administrators. The results of this study are: (1) the approach to build brand image is using social approach to the community and an interactive approach to establishing cooperative interactions with other organizations, an approach with community leaders so that they are known and trusted the wider community, (2) the method of build brand image is using direct or face-to-face meetings with the community and utilizing various media to build a positive impression in the community, (3) the technique in build brand image is using to utilizing verbal and visual media, (4) the brand image built by SDI Al Hidayah routine meetings of the institution's leadership by analyzing all programs, analyzing strengths and weaknesses, seeking and formulating consensus solutions to be followed up responsibly.